Upholding the integrity of the NCMP scheme - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2016)
Last Friday’s combative parliamentary debate on filling Ms Lee Li Lian’s vacated Non-Constituency Member of Parliament (NCMP) seat offered a foretaste of the dynamics between the ruling People’s Action Party (PAP) and the Workers’ Party’s (WP) in the 13th Parliament.